Hubungan Antara Keuntungan, Kinerja Keuangan, Pertumbuhan Perusahaan, dan Nilai Perusahaan di Indonesia - Aysyah Emy Maulidya; Djawoto Djawoto; Bambang Hadi Santoso (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background –The purpose of this study is to analyze profitability mediates the effect of financial performance and company growth on firm value in food and beverages companies. the recent phenomenon why your research is important. Aim –The data analysis method used is path analysis. The results of the study concluded that Current Ratio has an insignificant effect on Price Book Value, meaning that there is a problem with the company's capability to pay its short-term debt but not necessarily the company's value will decrease.. Design / methodology / approach –Debt to Equity Ratio has a significant effect on price book value, meaning that the higher the debt used by the company will increase profits so that it will affect the company's value. Asset Growth has an insignificant effect on Price Book Value, meaning that high asset growth will make the company need a lot of funds. Findings –Return on Assets is able to mediate the Current Ratio on Price Book Value, meaning that the increase in the current ratio value means more funds to finance operations and investments. Conclusion –Return on Assets is unable to mediate Debt to Equity Ratio on Price Book Value, meaning that a high or low debt to equity ratio owned will be equally risky. Research implication –Return on Assets is unable to mediate Asset Growth on Price Book Value, meaning that increasing profits will not affect asset growth..